Model Layanan Pendidikan Anak Berkebutuhan Khusus Di Sekolah Inklusi MI Nur Hidayah - Devina Istighfarin; Rahmah Ayu Andini; Dahlia Erviani Putri; Difa’ul Husna (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to provide information on the educational service models used for children with special needs, such as the mentally retarded and autistic. The research method used in this research is a qualitative method and a descriptive approach. Then the data collection technique is through observation by directly observing classes containing ABK children, interviews with the school principal and special accompanying teachers, and documentation. Data analysis techniques are carried out by reducing data, presenting data and drawing conclusions. The results of this research show that autistic and mentally retarded students have different learning outcomes and service models during the learning process are also different. Therefore, serving autistic and mentally retarded students requires special accompanying teachers so that the knowledge provided by educator can be more easily entered and understood.